Criminological Review of the Phenomenon of Cyberbullying - Asrum, Muhammad Ibnul; Thalib, Hambali; Jannah, Miftahul (Faculty of Law, Universitas Muslim Indonesia, 2024)
This study aims to determine the factors causing the occurrence of Cyberbullying crime in Makassar City and the efforts of law enforcement officers in tackling Cyber Crime in Makassar City. This study uses empirical methods. The location of the study was carried out in Polda South Sulawesi. The types and sources of data used are primary data and secondary data with data collection techniques, namely field research and literature research. The data obtained will be analyzed to produce conclusions and proposed descriptively qualitative and present clear data from the results of research conducted by the author. The results of this study indicate that the factors that influence cyberbullying in Makassar Information and communication technology such as mobile phones, video cameras, e-mail, and the web that can post or send disturbing, threatening, and humiliating messages that are intended to hurt others.so that anticipatory efforts are needed against cyberbullying, especially in the city of Makassar, therefore, comprehensive measures are needed to stem the level of cyberbullying cases in Makassar City through coordination of law enforcement authorities and community synergy. The author also includes suggestions as follows the establishment of the Criminal Code Bill is expected to formulate explicitly about the existence of bullying in cyberspace by including elements of repetitive or continuous behavior, attack and imbalance of power in the formulation of criminal acts, because the act of bullying in cyberspace is an act that can not be underestimated given the increasing dependence of society on online communication media. It is necessary to socialize to the general public about the dangers and consequences of cyberbullying and how to anticipate the influence of cyberbullying in using social media wisely and responsibly. Abstrak Penelitian ini bertujuan untuk mengetahui faktor-faktor penyebab terjadinya kejahatan Cyberbullying di Kota Makassar dan upaya aparat penegak hukum dalam menanggulangi kejahatan Cyber di Kota Makassar. Penelitian ini menggunakan metode empiris. Lokasi penelitian dilakukan di Polda Sulawesi Selatan. Hasil penelitian ini menunjukkan bahwa faktor-faktor yang mempengaruhi cyberbullying dalam Teknologi Informasi dan komunikasi Kota Makassar seperti ponsel, kamera video, e-mail dan web yang dapat memposting atau mengirim pesan yang mengganggu, mengancam dan memalukan yang dimaksudkan untuk menyakiti untuk itu diperlukan upaya antisipatif terhadap cyberbullying khususnya di Kota Makassar. Oleh karena itu diperlukan langkah-langkah komprehensif untuk membendung tingkat kasus cyberbullying di Kota Makassar melalui koordinasi aparat penegak hukum dan sinergi masyarakat. Pembentukan RUU KUHP diharapkan merumuskan secara tegas mengenai adanya intimidasi di dunia maya dengan mencakup unsur-unsur adanya perilaku berulang atau terus menerus, menyerang dan ketidakseimbangan kekuasaan dalam perumusan tindak pidananya, karena perbuatan intimidasi di dunia maya merupakan perbuatan yang tidak dapat dianggap remeh mengingat semakin bergantungnya masyarakat akan media komunikasi online. Sehingga, diperlukan sosialisasi terhadap masyarakat awam tentang bahaya dan akibat dari cyberbullying dan cara mengantisipasi pengaruh cyberbullying dalam menggunakan media sosial secara bijak dan bertanggung jawab.